Liner Shipping Connectivity and International Trade in Maritime Southeast Asian Countries - REZA Mohamad; SUTHIWARTNARUEPUT Kamonchanok; PORNCHAIWISESKUL Pongsa (Journal of International Logistics and Trade, 2015)
Liner connectivity plays an important role as a determinant in how a country is able to gain access to world markets. Liner shipping as the medium of seaborne transport for import and export of manufactured and semi-manufactured goods plays a significant part in international trade, which in turn potentially contribute towards the prosperity of a country and its surrounding region. Liner Shipping Connectivity Index (LSCI) is one of the most common benchmark to see how well connected a country in global trade, where it consists of five components, namely the number of ships, carrying capacity, ship size, services provided, and the number of companies that deploy container ships calling a country’s ports. This paper aims to tally from the most to the least which LSCI component contributes in improving the shipping connectivity with the most impact, in six Maritime South-East Asian countries, i.e., Indonesia, Malaysia, Philippines, Singapore, Thailand, and Vietnam. By descriptive statistics, correlation analysis, and panel data, this paper finds that the country port’s capacity to accept larger ship size provides the most significant impact towards the improvement of the connectivity in the region. To attract companies to deploy largest ship, the improvement needs to be complemented with the capacity that can meet the expected volume, offering a variety of service, and good turnaround speed at the country’s port. The paper is expected to present not only indicative recommendations on which logistics connectivity initiative needs to be invested first, but also necessary proposals to develop a programme for building the region’s overall logistics industry. Paper Code: SLC-206